The Jarisch-Herxheimer reaction in leptospirosis. - Vaughan, C. (BMJ Group, 1994)
Three patients with leptospirosis whose condition worsened after initiation of antibiotic therapy are reported. Their clinical deterioration appeared to be due to the development of the Jarisch-Herxheimer reaction rather than to progression of their underlying infection. Relevant aspects of the management of patients with leptospirosis are discussed.